Daily Beauty: A Reading of Bruni's Laudatio Florentinae Urbis - Strier, Richard (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2024)
This article is a close reading of Leonardo Bruni’s panegyric for the city of Florence (1404). It expands the discussion of the Laudatio Florentinae Urbis beyond the political context in which it has mostly, through the influence of Hans Baron’s pioneering work, been considered. It reads the text as a powerful assertion of Renaissance Humanism in its most secular, world-affirming mode. In exploring the value structure of the text, it finds the distinctly Aristotelian virtues ofmegaloprépeia (magnificence) and megalopsychia (great-souledness) structuring the text along with the Ciceronian and Aristidean virtue of humanitas. The article sees the appreciation of beauty as permeating the text, from its treatment of architecture, landscape, and city life to its treatment of the Florentine political institutions.